Immanuel Kant and theatre: to the problem statement - Korobko, Margaryta (Ukrainian Cultural Studies, 2024)
Background. On the occasion of the 300th anniversary of Immanuel Kant, this study is dedicated to exploring his influence on theatrical art, even though Kant himself did not show much interest in theater. The article attempts to examine the theater of his time, its presence in Königsberg, and the impact of Kant’s philosophy on the development of theatrical theory. To study the relationship between German theatrical art of the 18th century and the philosophy of Immanuel Kant, as well as to explore the influence of his philosophical ideas on the development of theatrical art in general. Methods. The article employs general scientific methods such as analytical, comparative, and generalization. Results. The analysis of Immanuel Kant’s influence on theatrical art is an atypical area of philosophical research. Although Kant did not leave any works specifically dedicated to theater, his aesthetic theories, particularly those presented in "the Critique of Judgment", had a significant impact on the development of theatrical art and its theory. Kant’s ideas, especially his concepts of the beautiful and the sublime, influenced Romanticism and notable figures such as Friedrich Schiller and Johann Goethe. The article also explores the historical context of theater development in Königsberg, where Kant lived and worked. Special attention is given to Kant’s role in establishing aesthetic ideas that became the foundation for subsequent changes in theatrical art. The article emphasizes that Kant’s philosophy remains relevant and influential in contemporary theater, providing new tools for analyzing and understanding aesthetic ideas. When considering the social role of theater and theatrical art, Kant also emphasized the importance of social interaction in the creation of art. He viewed aesthetic judgment as a serious act that is not merely private but concerns all of humanity. Aesthetic judgments form a public sphere, making them an important subject for philosophical analysis. According to Kant, aesthetic judgment is a way of seeking truth that unites people into a common human community. Similarly, theater is an instrument for seeking truth, a platform for questioning and finding answers to relevant issues. The article also highlights Kant’s significance for understanding theater as an art form that unites different types of creativity and reveals its potential for fostering aesthetic taste and moral values. Conclusions. Due to the lack of studies on the connection between Kant’s philosophy and theatrical art, there is a vast field for analyzing his influence on the aesthetics of theater, as confirmed by the history of theater during his lifetime.